Industrial Weed Control with Plainview SC - Randall S. Currie; Patrick W. Geier (Kansas Agricultural Experiment Station Research Reports, 2023)
The objective of this research was to determine application variable influence on Plainview SC (aminocyclopyrachlor/imazapyr/indaziflam) efficacy in an industrial setting. Plainview SC was applied at three rates and three application timings using two nozzle types to compare season-long weed control in noncropland. Late-season kochia control was best when Plainview SC was applied at 48 or 64 oz/a using flat-fan nozzles. Application timing did not affect these treatments. Similar control using the boomless nozzle required 64 oz/a of Plainview SC be applied either in fall or winter.
Keywords: Residual control; kochia; industrial weed control